Arcydzieła architektury i urbanistyki : polskie starówki / fot.: Waldemar Panów, Zbigniew Panów ; teksty: Michał Wiśniewski, Franciszek Ziejka. - Panów, Waldemar (1957- ). (Wydawnictwo BOSZ, 2013)
Album.